A high-accuracy, low-cost blood test for Alzheimer’s disease: validating P-tau181/Aβ42 in real-world cohorts - Dequan Liu; Dequan Liu; Hang Li; Hang Li; Qing Liu; Haiyan Li; Haiyan Li; Yuanyuan Tang; Kaiting Cheng; Tong Li; Tong Li; Yulan Chu; et al. (Frontiers in Aging Neuroscience)
ObjectiveTo evaluate the diagnostic performance of plasma P-tau181/Aβ42 measured via flow cytometry as a cost-effective tool for Alzheimer’s disease (AD) diagnosis.MethodsA cohort study involved 123 healthy controls, 60 AD/mild cognitive impairment (MCI) patients, 34 subcortical ischemic vascular disease (SIVD) patients, and 34 frontotemporal dementia (FTD) patients. Plasma P-tau181 and Aβ42 levels were measured using flow cytometry and cross-validated with Single-molecule Array (SIMOA). Publicly available Chinese cohort data were reanalyzed for comparative performance.ResultsThe P-tau181/Aβ42 ratio revealed significant differences between groups. A reference interval (0–0.109) achieved 96.2% diagnostic accuracy (95.0% sensitivity, 96.7% specificity) for AD versus controls, distinguishing AD from SIVD (88.3% accuracy) and FTD (86.2% accuracy). Flow cytometry-based P-tau181/Aβ42 showed 88.3% consistency with SIMOA-based P-tau217, while SIMOA-based P-tau181/Aβ42 achieved 92.3% accuracy.ConclusionFlow cytometry-based P-tau181/Aβ42 offers a cost-effective and accurate diagnostic method for AD, with performance comparable to SIMOA. This biomarker supports scalable AD screening in secondary healthcare settings, overcoming accessibility and cost barriers in resource-limited environments. This biomarker supports scalable AD screening in secondary healthcare settings, overcoming accessibility and cost barriers in resource-limited environments.